Cultura de la ilegalidad en Medellín y su asociación con diversas formas de violencia (2013)
ABSTRACT: To analyze and resume two previous author´s publications on magnitude of illegality culture in Medellin and metropolitan area, and its association with several violent aggressive forms. Methodology: Face to face household survey to a polietapic at at randon samble of 12 to 60 years of age Medellin and metropolitan area population, with a 94.6% answer proportion (n= 5781). Results: There is a very high illegality culture (44 a 72%). Illegality culture is negatively associated with children rearing practices, mainly with mother´s ones, and is very closed associate to iniquity perception. After living in a violent neighborhood, anomie is the principal risk factor to most of violence studied forms. Having a vigilant mother is a negatively associated factor to most of studied violent aggressive forms (associated to 80-90% armed assaults and 50% to unarmed robberies). Conclusion: There is a very high illegality culture in Medellin and metropolitan area, which seems to be product of iniquity perception, and appears to be associated to most of aggressions studied, and is lower only to association with living in a violent neighborhood.